The 2021 Chronic Kidney Disease Epidemiology Collaboration Race-Free Estimated Glomerular Filtration Rate Equations in Kidney Disease: Leading the Way in Ending Disparities - Keyerra Charles; Mary Jane Lewis; Elizabeth Montgomery; Morgan Reid (Mary Ann Liebert, 2024)
Purpose: In 2020, the National Kidney Foundation (NKF) and the American Society of Nephrology (ASN) convened a Task Force to recommend an evidence-based race-free approach to estimated glomerular filtration rate (eGFR). After the rigorous review of more than 20 approaches, the NKF/ASN Task Force published the final report that recommended the implementation of the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI 2021) equation for eGFR using creatine and expanded utilization of cystatin C testing. The purpose of this manuscript is to provide a comprehensive overview of the evolution of eGFR equations, and an overview of the Task Force deliberations and recommendations. For over two decades, the equation recommended to calculate eGFR included a race coefficient to adjust for data that suggested that American adults with African ancestry had consistently higher serum creatinine levels. Methods: We will provide a discussion illustrating why the 2021 CKD EPI equations are the most equitable solution to eGFR. We will also provide an overview of the current implementation status and best practices for the new equations. Lastly, we will discuss how deployment of the new equations is an important step toward eliminating significant disparities in CKD care which disproportionately affect communities of color. Results: Removing race from the algorithm used to assess kidney function is most equitable. Since race is a social construct, its use in clinical algorithms has facilitated health disparities in Black/African American people, Hispanic/Latino people, and other racial and ethnic minority groups?those who are already disproportionately impacted by diabetes, hypertension, and kidney disease. In turn, these same individuals experience significant inequities in kidney health care including reduced access to nephrology care, home dialysis, and kidney transplant. Conclusions: Adoption of the race-free 2021 CKD-EPI eGFR equations will have life changing implications for kidney health. It will aid in appropriate referral, identification, diagnosis, treatment, and management of kidney disease and transplantation services/options. The outcomes of widespread implementation of the new equations coupled with system change quality improvement interventions such as the kidney profile will lead to more equitable outcomes and begin to address the crippling disparities in early, appropriate testing for CKD.